Three-dimensional printing for laparoscopic partial nephrectomy in patients with renal tumors. Issue 9 (September 2019) - Fan, Gang; Meng, Yanbin; Zhu, Shuai; Ye, Mingji; Li, Mingfeng; Li, Feiping; Ye, Yuanchun; Liu, Zhizhong; Weiqin, Han; Xie, Yu
Objectives: To explore the efficacy of three-dimensional printing physical model-assisted laparoscopic partial nephrectomy (3D-LPN) in patients with renal tumors. Methods: We retrospectively assessed all patients who underwent LPN with or without 3D-printed physical model assistance from January 2016 to February 2018 at our institution. The demographic characteristics, operative findings, and clinical outcomes from the procedure were collected and analyzed. Results: Sixty-nine patients underwent 3D-LPN and 58 underwent traditional LPN. The groups showed no differences in demographics, RENAL score, surgical approach, operative time, estimated intra-/postoperative blood loss, increased creatinine level, or complications. In the 3D-LPN group, warm ischemia time was shorter, whereas surgery waiting time was longer, compared with those parameters in the LPN group. Subgroup analysis indicated that for patients with RENAL score ≥8, the 3D-LPN group had significantly shorter warm ischemic time and less intraoperative blood loss than the traditional LPN group. Intra- and postoperative hospital complication rates were similar for 3D-LPN and traditional LPN groups (8.7% vs. 13.7%). Conclusions: 3D printing provides an additional tool to assist with LPN. Use of a 3D model can assist in planning and performance of LPN in patients with RENAL score ≥8.